A comparative evaluation of haematological and biochemical parameters of Nemipterus randalli and Pagellus erythrinus species living in Gökova Bay, Türkiye - Rifat Tezel; Ümit Acar; Sercan Yapıcı (PeerJ)
This study aims to determine and compare the reference values of the haematological and biochemical blood parameters of two fish species collected from the Gökova Bay (Muğla, South-Western of Türkiye): the non-native and invasive Randall’s threadfin bream, Nemipterus randalli and the native Common pandora, Pagellus erythrinus. Both species inhabit the same environment and compete for resources. Blood samples were collected from a total of 100 fish samples (50 N. randalli and 50 P. erythrinus) which were caught from a depth of 30 to 60 meters between February 2023 and July 2024. Therefore, sampling could be carried out in summer and winter seasons when the water temperature varies significantly. The results indicate that red blood cell (RBC), haemoglobin (Hb) and haematocrit (Hct) levels significantly increases in summer (p < 0.05). Statistical analyses revealed that all of the haematological parameters of N. randalli are higher than the P. erythrinus (p < 0.05). In terms of serum biochemical parameters, glucose (GLU), triglyceride (TRIG), cholesterol (CHOL), total protein (TP), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) levels of two species had showed no significant difference in both summer and winter samples (p > 0.05). However, serum alanine aminotransferase (ALT) levels of N. randalli were statistically significant different compared to P. erythrinus in summer and winter samples (p < 0.05). Additionally, the highest lactate dehydrogenase (LDH) value was measured from N. randalli in summer sampling and this was found to be significantly different from other groups (p < 0.05). Multidimensional scaling (MDS) analysis revealed differences between the blood parameter results of N. randalli and P. erythrinus individuals. This study provides important data about the physiological adaptations of haematological and biochemical blood parameters of the two species to environmental factors. The similarity in haematological and biochemical parameters revealed the possibility that N. randalli could distribute to new habitats where P. erythrinus is distributed. This suggests a further potential distribution of the invasive N. randalli and the need for a careful monitoring.